Association between estimated glomerular filtration rate and outcomes in patients with diabetic foot ulcers: a 3-year follow-up study. Issue 1 (July 2017) - He, Yang; Qian, Hongjie; Xu, Lei; Zhang, Shanshan; Gu, Xueming; Gu, Junyi; Shi, Jianyuan; Shen, Yaping; Liu, Jianmin; Tang, Zhengyi
Abstract : Objective: End-stage renal disease and dialysis have been proven to be associated with poor prognoses in diabetic foot ulcers (DFUs). However, it has rarely been reported whether and to what extent milder renal insufficiency affects the prognosis. The purpose of this study was to investigate the categorized impact of estimated glomerular filtration (eGFR) on the outcomes of patients with DFU. Design and methods: Three hundred and sixty-six DFU patients hospitalized in a Chinese tertiary hospital were recruited and classified into 4 groups according to the eGFRs as follows: normal (≥90), mildly reduced (60–89), moderately reduced (30–59), and severely reduced (<30). These patients were followed-up for an average of 37 months to observe the outcomes, including ulcer healing, amputation, ulcer recurrence, cardiac or cerebrovascular events and death. The associations between eGFR and the outcomes were analysed by Cox proportional-hazards models. Results: Compared to patients with normal eGFR, patients with moderately reduced eGFR had higher risk of healing failure (hazard ratio (HR) = 2.08, 95% confidence interval (CI): 1.13–3.82), cardiac events (HR = 5.25, 95% CI: 2.17–12.89) and death (HR = 3.54, 95% CI: 1.36–9.20). Severely reduced eGFR was associated with higher incidence of healing failure (HR = 2.84, 95% CI: 1.25–6.49) and death (HR = 4.45, 95% CI: 1.23–16.07). The impact of eGFR on ulcer recurrence and cerebrovascular events was not observed in all groups. Conclusions: Moderately and severely reduced eGFR in patients with DFU were independent predictors for poor prognoses of both the limbs and the patients.